Actividad en el Paraninfo Daniel Oduber en la UNED.
En la mesa principal de izquierda a derecha Luis Guillermo Carpio Malavassi, Juan Carlos Parreaguirre Camacho, Rodrigo Arias Camacho, René Muiños Gual y Vigny Alvarado Castillo